Strategi Digitalisasi sebagai Upaya Peningkatan Pelayanan di Kantor Kementerian Agama Kota Batu - Bella Natania Anisa; Siti Lutfiachi Zar’an (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to examine the digitalization strategy implemented by the Batu City Office of the Ministry of Religious Affairs in improving the quality of public services. Digital transformation has been a strategic step taken since 2018, along with the demand to realize services that are transparent, efficient, and free from extortion practices. Various digital innovations have been developed, including the use of the Srikandi application for correspondence administration, as well as the launch of the PELESIR KE BATU and RELIGI platforms as integrated electronic service facilities. Through interviews with internal parties, it was found that digitalization was able to simplify the service process from submission to submission of documents online with Electronic Signatures (TTE). Despite experiencing technical problems due to national system disruptions, Kemenag Batu showed adaptability by utilizing backup solutions such as Google Drive and spreadsheets. Counseling and training efforts were also made to improve the digital literacy of the community and service officers. The results of this study show that the digitalization strategy has had a positive impact on improving the quality of public services within the Ministry of Religious Affairs of Batu City.